The Impact of Online Game Addiction on Work Productivity Among Individuals Residing in Urban Areas of Indonesia - Yanuar Fahrizal; Fatin Indira (Poltekkes Kemenkes Surakarta, 2025)
Background: Indonesia exhibits high smartphone penetration (210.77 million users, 2021) and substantial online gaming engagement, with 26% of gamers aged 18–24 and 20% aged 25–34. Given alarming gaming disorder prevalence (IGD: 14.6% males, 6.2% females; GD: 7.2% males, 2.8% females) and limited research on productivity impacts in urban Indonesia, this study investigates online game addiction's effect on work productivity among young adults in South Jakarta. Methods: A cross-sectional correlational design recruited 95 participants via purposive sampling (aged 18–26, South Jakarta residents, >3 hours/day non-professional gaming). Data collection utilized the validated Indonesian Online Game Addiction Questionnaire (7-item, Cronbach’s α=0.73) and Individual Work Performance Questionnaire (18-item, Cronbach’s α=0.814–0.871). Normality was confirmed with Kolmogorov-Smirnov testing; SPSS v.28 facilitated Pearson correlation and linear regression analyses. Results: Participants were predominantly male (64.21%), high school-educated (72.63%), and private sector employees (61.05%). Key findings revealed: a significant weak negative correlation between online game addiction and work productivity (r = -0.291, p = 0.04); a strong positive correlation between addiction and gaming duration (r = 0.486, p < 0.001); no correlation between gaming duration and productivity (p = 0.312); and regression indicating addiction explains 9.7% of productivity variance (Adjusted R² = 0.088, β = -0.420, p = 0.002). Conclusion: Online game addiction significantly impairs work productivity among urban Indonesian youth, yet accounts for only 9.7% of variance—underscoring the influence of unaddressed mediators like sleep quality and motivation. Findings necessitate integrating psychiatric nursing interventions within workplace mental health frameworks.